Among Notes on the Margin: the Legacy of an “Unruly” Discipline - Kozik, Ewa (Studia Etnologiczne i Antropologiczne, 2020)
The aim of this article is to re-examine the methodology of ethnographic research vis a vis the influence of methodology on the shaping of ethnology and cultural anthropology as a scientific discipline. Field research, which presupposes the scholar’s active participation and involvement in the life of the group under investigation, as well as the accompanying challenges to such an approach, are here treated as elements that shape the heritage of ethnology, reinforcing its power and securing its place among other disciplines. The author has undertaken the anthropological analysis of excerpts from field notebooks and subjective records by scholars involved in the creation of the Polski Atlas Etnograficzny [Polish Ethnographic Atlas].